Carnivores as zoonotic parasite reservoirs in ancient times: the case of the Epullán Chica archaeological cave (Late Holocene, northwestern Patagonia, Argentina) - Beltrame, María Ornela (2018)
Zoonoses are currently considered as one of the most important threats for Public Health worldwide. Numerous zoonoses known today have occurred since antiquity. Carnivores act as definitive hosts for many intestinal parasites; some of them are responsible for several zoonotic diseases. The aim of this work was to study the parasite remains found in coprolites assigned to carnivores from the archaeological site Epullan Chica (ECh) and to discuss the results from a zoonotic point of view. ECh is located in northwestern Patagonia, Argentina and was occupied since the end of the Late Holocene (∼2200 years B.P.). Nine coprolites were examined for parasites. Samples were processed by rehydration in a 0.5 % water solution of trissodium phosphate, followed by homogenization, filtered and processed by spontaneous sedimentation. The macroscopic remains were separated and dried at room temperature and were examined for diet analysis. Six out of 9 coprolites examined were positive for parasites. Representatives of at least 10 parasite taxa were registered. Results are in line with the reconstruction of the scenario of zoonoses in the past and the diseases that the human populations and animals from Patagonia could be exposed. The present study provides the first palaeoparasitological report of carnivore coprolites recovered from the archaeological site Ech and reflects contamination of the cave used by hunter-gatherers with different parasites causative of zoonotic diseases.